Transcription infidelity and genome integrity: the parallax view. Issue 5 (20th October 2018) - Gordon, Alasdair J.E.; Sivaramakrishnan, Priya; Halliday, Jennifer A.; Herman, Christophe
ABSTRACT: It was recently shown that removal of GreA, a transcription fidelity factor, enhances DNA break repair. This counterintuitive result, arising from unresolved backtracked RNA polymerase impeding DNA resection and thereby facilitating RecA-loading, leads to an interesting corollary: error-free full-length transcripts and broken chromosomes. Therefore, transcription fidelity may compromise genomic integrity.